Analisis Pengukuran Kinerja BPRS Jawa Timur dengan Maqashid Sharia Index dan Profitability - Perdana, Tegar Hanif (Diponegoro Journal of Islamic Economics and Business, 2023)
Sharia banking in order to win the competition needs to establish trust in stakeholders both in terms of financial performance as well as sharia and social performance. This study aims to determine the performance of East Java BPRS with the Maqashid Sharia Index and Profitability. The method used is through non-statistical quantitative research techniques and qualitative descriptive techniques. by analyzing the financial reports of BPRS East Java for the period 2017 to 2021. Research shows that measuring the performance of maqashid sharia BPRS in East Java in the period 2017-2021 in terms of the Maqashid Syariah Index (MSI) aspect, produces an average MSI value of 3.55226. The BPRS that received the highest score for MSI achievement was BPRS Amanah Sejahtera with a score of 0.33048, while the BPRS that received the lowest score for MSI achievement was BPRS Karya Mega Sentosa with a score of 0.20953. Meanwhile, the measurement of BPRS sharia financial performance in East Java in the 2017-2021 period in terms of Profitability yields an average value of 0.0461